The Protective Effects of Empathic Concern and Optimism on Emotional Exhaustion - Wong, Yoko; Sun, Jing; Yu, Lifang (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aims to investigate the relationships between emotional exhaustion, empathic concern, and dispositional optimism in a diverse sample of professionals. The primary objective is to determine how empathic concern and dispositional optimism predict levels of emotional exhaustion. A cross-sectional study design was employed with a sample of 300 participants drawn from healthcare, education, and corporate sectors. Participants completed the Maslach Burnout Inventory for emotional exhaustion, the Interpersonal Reactivity Index for empathic concern, and the Life Orientation Test-Revised for dispositional optimism. Pearson correlation coefficients and linear regression analyses were conducted using SPSS version 27 to examine the relationships between the variables. The results indicated significant negative correlations between emotional exhaustion and both empathic concern (r = -0.45, p < 0.001) and dispositional optimism (r = -0.52, p < 0.001). Linear regression analysis showed that empathic concern (β = -0.31, p < 0.001) and dispositional optimism (β = -0.39, p < 0.001) were significant predictors of emotional exhaustion, explaining 42% of the variance (R² = 0.42, F(2, 297) = 52.34, p < 0.001). The findings suggest that higher levels of empathic concern and dispositional optimism are associated with lower levels of emotional exhaustion. These results underscore the importance of fostering empathy and optimism in professional settings to enhance psychological resilience and reduce burnout. Interventions aimed at increasing empathic concern and dispositional optimism could be beneficial in mitigating emotional exhaustion among professionals.